Cover Picture: Plasma Process. Polym. 9∕2017. Issue 9 (15th September 2017) - Ambujakshan, Arun T.; Sadek, Abu; Magniez, Kevin; Mateti, Srikanth; Mayes, Edwin; Devi, Gayathri; Pringle, Jennifer M.; Plessis, Johan du; Chen, Zhiqiang; Corr, Cormac S.; Hodgson, Peter D.; Dai, Xiujuan J.
Abstract : Front Cover: The reactive plasma species nitrate (NO3 ‐) and hydrogen peroxide (H2 O2 ) were produced in high selectivity in water using air and argon, respectively, in a needle and plate electrode assembly. The plasma treated water was used as an efficient and environmentally friendly electrolyte for anodizing titanium metal. The NO3 ‐ from air plasma is the key factor in the formation of TiO2 nanotubes and the H2 O2 from the argon plasma assists the oxidation process. Further details can be found in the article by A. T. Ambujakshan et al. on page1600219 .